Developing the fifth generation port concept model: an empirical test. Issue 3 (13th August 2018) - Lee, Paul Tae-Woo; Lam, Jasmine Siu Lee; Lin, Cheng-Wei; Hu, Kai-Chieh; Cheong, Inkyo
Abstract : Purpose: The purpose of this paper is to test the 5GP concept with measurement of the performance of Busan, Hong Kong, Singapore and Shanghai ports, employing a hybrid method of consistent fuzzy preference relation (CFPR), VIsekriterijumska Optimizacija i KOmpromisno Resenje (VIKOR) and PROMETHEE. Design/methodology/approach: The authors developed the concept of the fifth generation ports (5GPs), and apply CFPR, VIKOR and preference ranking organization method for enrichment evaluations (PROMETHEE) to evaluate the 5GPs. Findings: The performance of the ports of Hong Kong and Singapore is close to meet the definition of 5GP criteria. On the contrary, ports of Busan and Shanghai are still behind the 5GP stage in light of the majority of the evaluation criteria's performance. Research limitations/implications: This paper studies four ports. More empirical tests are needed to verify the applicability of the 5GP concept toward other ports. Practical implications: The findings provided port managers with the insight of how to improve their port to meet the criteria of 5GP. Social implications: New criteria and higher expectations of existing requirements present challenges to port managers for a need to raise the bar of service standards and develop new competencies. Originality/value: The authors developed the concept of the 5GPs. Newly developed 5GP contributes to expanding the concepts of first to fourth generation ports developed by UNCTAD.